2020
DOI: 10.3390/agronomy10040516
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellic Acid Can Improve Seed Germination and Ornamental Quality of Selected Cyclamen Species Grown Under Short and Long Days

Abstract: Cyclamen species (swinebread spp.) are perennial herbaceous plants which belong to the Primulaceae family, widely used as medicinal or ornamental plants. Currently, gibberellic acid (GA3), an environmentally friendly bioregulator is widely used to enhance the productivity and phenotypic characteristics of multiple ornamental crops. A dual experiment was conducted to evaluate the influence of gibberellic acid (50, 100 or 150 mg/L), on germination earliness of seeds, along with growth and ornamental quality of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…1 Effect of seed treatment on seed germination and seedling growth before forced ageing Fig. 2 Effect of seed treatment and forced ageing on seed germination and seedling growth at 5 th day of forced ageing Rice and Ornamental plant (Cyclamen species) treated with foliar application of GA 3 improved the germination percentage of resultant seeds (Wang et al, 2019;Cornea-Cipcigan et al, 2020). Seed treatment with GA 3 has been resulted in the highest germination percentage in tomato (Balaguera-Lopez, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Effect of seed treatment on seed germination and seedling growth before forced ageing Fig. 2 Effect of seed treatment and forced ageing on seed germination and seedling growth at 5 th day of forced ageing Rice and Ornamental plant (Cyclamen species) treated with foliar application of GA 3 improved the germination percentage of resultant seeds (Wang et al, 2019;Cornea-Cipcigan et al, 2020). Seed treatment with GA 3 has been resulted in the highest germination percentage in tomato (Balaguera-Lopez, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Rice and Ornamental plant (Cyclamen species) treated with foliar application of GA 3 has been improved the seedling vigor index of resultant seeds (Wang et al, 2019;Cornea-Cipcigan et al, 2020).The film formed around the seed in seeds coated with SCF I and II, it act as a physical barrier, which has been reported to restrict oxygen diffusion to the embryo (Dheerajet al, 2018) and may reduce the catabolic activity or food reserve degradation. Hence, it may be the reason for seed viability and vigour maintenance in onion by SCF I and II during forced ageing.…”
Section: Resultsmentioning
confidence: 99%
“…GA 3 significantly increased SL and SGR by approximately 250.0% and 150.0% than the control when Han NW seeds were treated with 1000 mg•L −1 of GA 3 and Morpeth seeds treated with 500 mg•L −1 of GA 3 , respectively. Cornea-Cipcigan, et al [46] reported a higher plant height with increased seedling vigour in Cyclamen species (swinebread spp.) when plants were treated with foliar application of GA 3 .…”
Section: Gibberellic Acid May Decrease Seed Germination But May Promote Early Growth Of Industrial Hempmentioning
confidence: 99%
“…In hormonal priming, plant growth regulators like gibberellic acid (GA 3 ), abscisic acid (ABA), or salicylic acid (SA) have been used more commonly. GA 3 plays a significant role in plant growth and development, such as seed germination, stem elongation, leaf expansion, flower and fruit development, and floral transition (Cornea-Cipcigan et al 2020). They are frequently used to overcome seed dormancy and improve seed germination in many species by activating embryo growth, mobilizing reserves, and weakening the endosperm layer (Pallaoro et al 2016).…”
Section: Introductionmentioning
confidence: 99%